Breathing beyond borders: Reclaiming BIPOC knowledges and methodologies in drama therapy. Issue 1 (1st April 2023) - Williams, Britton; Lepere, Refiloe
This editorial reflects on the urgent need for literature that reflects Black, Indigenous and People of Colour (BIPOC) theories, practices and methods. This Special Issue investigates the social and cultural contexts that support and enable decolonial practices of theorizing and healing. The authors herein experiment with different forms of resistance, imagine new research methodologies, engage collective imagination, and lift and re-cover cultural wisdom through their contributions. Calling on ancestral, cultural and embodied knowledge, the contributors to this Special Issue unsettle default assumptions and expectations regarding knowledge, theory and practice in drama therapy and beyond.